Analisis Emosi Dasar pada Film Animasi 3D Ficusia dengan Metode Semiotika Charles Sanders Peirce - Putri, Wenny Febrina; Prasetiya, Happy Yugo (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2025)
Constructing basic emotions in the facial expressions of 3D characters is a complex and time-consuming process, yet it plays a vital role in non-verbal communication by enabling audiences to recognize emotions and understand character traits in animated films. This study aims to address the gap in analyzing how basic emotional signs are represented in animation to support more communicative character design. A descriptive qualitative approach was applied using Charles Sanders Peirce’s semiotic framework of trichotomy, which explores the relationship between sign, object, and interpretant in the facial expressions of the main character. The findings reveal that six basic emotions can be identified through iconic signs, where facial expressions represent specific emotional states, and their meanings are interpreted by the audience. These results demonstrate that Peirce’s semiotics offers an effective approach for analyzing emotional representation in 3D animation and contributes to the development of structured facial expression design strategies. Such strategies not only enhance non-verbal communication, but also strengthen emotional engagement and reinforce character identity in animated storytelling.